The Ethics of In-company Research: An Exploratory Study - Maxwell, G. (Journal of business ethics, 2004)
This paper seeks to advance ethical practice in business and integrate ethics with management curricula. It focuses on the ethical dimensions of in-company research conducted by human resource practitioners who are part time students on a postgraduate research degree award (M.Sc. in HRM). These dual roles of academic researcher in HRM and HR practitioner can become blurred and present particular ethical considerations. Beyond ethical perspectives of HRM, the paper investigates the ethics of in-company research in terms of conceptual and operational factors. The main conclusion is that ethical guidelines need to be developed for M.Sc. in HRM students. Draft guidelines are offered as the basis for development.